A BIBLIO-TEXTUAL STUDY AND EDITION OF THE POEMS OF ANDREW MARVELL (1970)
The introduction of recent bibliographic techniques into editorial practice raised hopes of finally finding objective solutions to many seemingly insoluble textual problems. Yet as the eminent bibliographer Fredson Bowers points out (Bibliography and Textual Criticism, 1964) such hopes - either because the techniques are still not completely developed, or because of their inherent limitations - have not been fully realised. Walter Greg, another pioneer in the field, had earlier warned that the new techniques could not be expected to carry the textual critic the whole way to perfection (Bibliography - An Apologia, 1932). The present thesis represents an attempt to apply the techniques to, and to overcome their limitation in, the editing of Marvell’s poems - with what success the sequel will show. Chapter 1 considers the circumstances surrounding the first printing of most of Marvell’s poems in 1681 at the instance or with the connivance of that Mary Palmer who falsely claimed to be his widow. It is shown that certain items intended for inclusion in the Miscellaneous Poems were cancelled because o£ the political upheavals of the year; that these cancelled poems deal with Cromwell and would have been likely to mind the public at the Civil war and the Regicide at a time when repetition of both catastrophes had been narrowly averted; that because the cancellations, the 1681 edition actually survives in three states. It is further suggested that the volume was printed by ‘casting-ort’ the copy, that, during printing, other materials not supplied by Mary Palmer were added, and that none of those directly concerned with the printing can be expected to have exercised salutary control over the process of publication. Chapter 2 discussed the various theories of textual criticism evolving from editorial practices in the fields of Biblical, Classical, and Modern Bibliographical scholarship. The objective common to all three is the determining of the text closest to the author's original by tracing the descent of surving copies through the use of various methods: by Dom Quentin's theory of intermediaries, by Paul Maas’s system of stemmatics, by Walter Greg’s calculus of variants and the like. For Marvell, with only one edition to be followed, the common problem of preferring one of a series of early editions does not exist; the real difficulty is to ascertain the poet’s own intention whenever there is a cause for doubt, always bearing in mind the not-too-favourable ambiences of poems either published posthumously or circulated anonymously. In addition to the problem of establishing Marvell’s intention in authenticated poems attributed to his authorship. The conclusion is that because of the peculiarities of transmission and survival, an edition of Marvell’s poem must necessarily be based not upon one but upon several methods of approach. Chapter 3 examines the background and technique of the ‘copy-text|’, the use of which is made obligatory by the repeated successes of the bibliographic school of textual critics in its application to earlier English works. Where only one copy of questionable superiority can be singled out, no one need quarrel with this technique; difficulties begin to arise when there are several copies of comparable authority available. To insist upon a ‘copy-text’ even in this case is justified by what Greg calls the ‘accidentals’ of a text (i.e. the spelling modes, the punctuation system, etc.). It is even more justified when it ensures that a modern edition retains significant ‘accidentals’, whatever they be, to the point where all linguistic traits of the author’s period, all significant indications of linguistics and philological peculiarities, whether temporal, or social, or private, should be transmitted through the text. In case of Marvell, the setting-up of a ‘copy-text’ without thorough exploration of ‘accidentals’ is scarcely feasible. That completed, the final question is the degree to which the results of the exploration, the resolutions of the difficulties it reveals, must be followed. Chapter 4 considers many of the peculiarities of the English language in Marvell’s time, particularly those (consequent upon the tangle of vowel-shifts known as the Great Sound Shift) which have immediate effectiveness for the ‘copy-text’ technique. Thanks to research by philologist-linguists like Luich, Sweet, Wyld, Whitehall, Dobson, Nist, Trager- Smith, et al., the overall pattern of Early Modern English, particularly that of the sonantal system, emerges with some clarity. Here, the results are schematized on a phonetic basis, and the confusions that might confront an editor, especially those reflected on spellings and rhymes, are broadly charted. From this exercise emerge several linguistic guide-lines to be followed, or at least considered in editing Marvell. Chapter 5 attempts to demonstrate how the study of para-linguistic factors of metre, rhythm, rhyme, and repetitive sound-patterning facilitates the editorial task, especially for rhymed verse. Here the metre and rhythms of Marvell’s verse are analysed in some detail and from several point of view. The most obvious prosodic feature is the maintenance of a strict syllable count- so strict that any apparent violation can be attributed to an error of transmission. In the octosyllabic couplet, his favourite form, Marvell not only makes good use of traditionally accepted variations, modulations, and metrical equivalences but is also able to absorb into his verse the principles of the ‘Classical plain style,’ the so-called sermo. In him, this is not merely a matter of achieving post-Elizabethan elegance and colloquial ease of diction and syntax; it also, and more importantly, involves the natural ordering of syntactic units in such a fashion that the pauses bordering segmenting them can be varied as freely and unaffectedly in verse as they normally are in prose and speech- all these within the strict metrical framework of syllable count. As a result, there is remarkable free positioning of the ‘caesuras’, which fall at various places in a line after odd- as well as even-numbered syllables and not- as advocated by certain Elizabethan posts and authorities- in a fixed medial position. Following the method of Ants Oras (Pause Patterns in Elizabethan and Jacobean Drama, 1960), an attempt is made to graph pause distribution profiles for the two famous poems “To His Coy Mistress” and “AN Horatian Ode” on the basis of both printed punctuation and syntactic analysis of actual readings. Chapter 6 brings forward the argument that capitalization is a device employed to indicate emphasis- particularly in stress bearing words of a poem- and is therefore an important ‘accidental’ to be reckoned with in editing verse. This fact is revealed in the analysis of Marvell’s On a Drop of Dew, and is confirmed by the practice of contemporary poets, by printing practice, and by statements of primers at tile time. What emerges is that this poem as printed in 1681 (and probably some other poem), seems to have fewer printed capitalized words than appeared in the original manuscript. In editing the poems, while it may not be possible to restore all the capitalization that Marvell intended, it is at least possi1ble to detect words wrongly capitalized, if they destroy what seems to be the intended rhythm and sense. Chapters 7 to 9 deal with the problem of attributing to Marvell some poems written anonymously. In Chapter 7 the various methods of determining the authorship of disputed works are reviewed. These fall into two main groups: internal evidence of style and ideas, the external evidence of direct statements by the author or his contemporaries, or statements from letters, diaries, and so forth. For Marvell external evidence is found to be rather weak – sometimes a contradictory. Internal stylistic evidence is relatively unhelpful mainly because the characteristic styles of the lyrical poems are different from those of the political poems. On the other hand, evidence from ideas seems important because of the feasible comparison between the views expressed in his prose written and those in the political poems. For this purpose, Marvell’s activities and attitudes as a politician are examined in Chapter 8. The picture given is that of a loyal citizen with a deep reverence for law and the constitution and a strong belief in the providential guidance of affairs of state. In a mixed constitution such as that of England at the time when the political poems were written, Marvell was determined to support equally the prerogatives of the King and the privileges of Parliament; and rejected any section – from parliament or King - that might upset the balance. -Finally, in Chapter 9, the political poems attributed to Marvell are re-examined individually. After this consideration, only four of the sixteen poems printed by Margoliouth - The Last Instructions, The Loyall Scott, Bludius et Corona and Scaevola Scoto-Brittannus –are found to be fully acceptable as Marvell’s. Four others – Clarendon’s House-Warming, Britannia and Rawleigh, and the Second and Third Advices are probably his. All the others, it appears, have been wrongly ascribed to him.